The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M.; Brown, Mary H. (Thomson Delmar Learning, 2007)
Keywords: Handbooks; manuals; etc; Pediatric nursing; dept.nur; faculty_collection

Enhancing evidence bases for interventions in a baccalaureate program. - Aronson, Barbara S; Rebeschi, Lisa M; Killion, Susan Westrick (Nursing education perspectives, 2007)
Modifying the sequence, objectives, and research-based content for a nursing interventions course in a baccalaureate curriculum resulted in improved outcomes including enhancement of the evidence bases for nursing interventions. A mixed methods research study demonstrated better student preparation for clinical experiences and improved satisfaction with course content, consistency, and sequencing. Faculty reported improved integration of theory, research, and practice. Although grades were slightly lower in the new course, the positive outcomes greatly outweighed this expected finding. A foundation for improving the evidence bases for future nursing practice is guided by the curricular modifications described in this article.
Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, USA. aronsonb1@southernct.edu
Keywords: *Attitude of Health Personnel; *Curriculum; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Evidence-Based Medicine/ed [Education]; *Nursing Research/ed [Education]; *Students; Nursing/px [Psychology]; Attitude of Health Personnel; Clinical Competence; Connecticut; Curricular and course development; Curriculum; Curriculum/st [Standards]; Diffusion of Innovation; Education; Nursing; Baccalaureate; Evidence-Based Medicine; Evidence-based interventions; Faculty; Nursing; Focus Groups; Health Knowledge; Attitudes; Practice; Health Services Needs and Demand; Humans; Nursing Education Research; Nursing Methodology Research; Nursing Research; Organizational Objectives; Program Evaluation; Qualitative Research; Questionnaires; Skills laboratory; Student learning outcomes; Students; Nursing; Surveys and Questionnaires; United States; article; attitude to health; clinical competence; curriculum; dept.nur; education; evaluation; evidence based medicine; health care quality; health personnel attitude; health service; human; information processing; mass communication; nursing education; nursing methodology research; nursing research; nursing student; organization; organization and management; peer-reviewed; psychological aspect; qualitative research; questionnaire; standard; ⛔ No DOI found

Registered nurses and delegation. - Saccomano, Scott J (The Pennsylvania nurse, 2007)
Place: United States Saccomano, Scott J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Delegation; Professional/og [Organization & Administration]; *Nursing Assistants/og [Organization & Administration]; *Nursing Staff/og [Organization & Administration]; *Nursing; Supervisory/og [Organization & Administration]; American Nurses' Association; Clinical Competence; Delegation; Professional; Humans; Licensure; Nursing; Nurse's Role; Nurses' Aides; Nursing Assistants/ed [Education]; Nursing Staff; Nursing; Supervisory; Practice Guidelines; Practice Guidelines as Topic; Professional Autonomy; United States; clinical competence; dept.nur; education; human; licensing; medical society; nurse attitude; nursing; nursing assistant; nursing staff; organization and management; practice guideline; professional delegation; professional practice; review; ⛔ No DOI found